The true female of Heteropoda squamacea Wang, 1990 (Araneae: Sparassidae) - Liu, Jie; Li, Shuqiang; Jäger, Peter (Zootaxa, 2008)
Besides the genus Olios Walckenaer, 1837, Heteropoda Latreille, 1804 is the most diverse genus in the spider family Sparassidae. Currently, a total of 192 Heteropoda species are known, among them 13 from China (Platnick 2008). In the current paper, the female of Heteropoda squamacea Wang, 1990 is described for the first time. The previously proposed female of H. squamacea appeared to be a misidentification of H. venatoria (Linnaeus, 1767) (Jäger & Yin 2001). Another female paratype of H. squamacea falls into the variation scheme of H. tetrica Thorell, 1897 (Eusemann & Jäger, in press) and most likely belongs to this species. Due to congruence of palpal structure, especially the bifurcated tip of the conductor, H. bifurcuta Wang, Chen & Zhu, 2002 (not: H. bifurcula; contra Platnick 2008) is considered as a junior synonym of H. squamacea.